Tracing the optimal level of political and social change under risks and uncertainties: Some lessons from ancient aparta and Athens - George E. Halkos; Emmanouil Marios L. Economou; Nicholas C. Kyriazis (Journal of Risk and Financial Management, 2022)
The present paper is inspired by the notions of "financial risk" and "financial uncertainties" and transfers their basic reasoning to social science analysis; that is, it develops a theoretical analysis in order to explain social and political change. We know that the degree of social and political change depends on the set of established institutions in a society. Societies can face two extremes: volatility, e.g., rapid changes that lead to instability, which increases the risk of a system or regime collapsing, or rigidity, which does not permit necessary adaptation and change and thus may again increase the risk of the regime collapsing. Thus, an optimal (or ideal) point of change is between the two extremes, permitting change that is neither too sudden and fast nor too slow and inflexible. To illustrate this, we analyze two cases from ancient Greece: Sparta, as a society and state with too many institutional checks and balances that led to rigidity and collapse, and Athens, which in the 5th century BCE had an institutional setting with very limited checks and balances, which again led to near collapse until the late 5th century BCE, when new institutions that were related to some efficient checks and balances were introduced that enabled the state to survive in a world of changing circumstances and balances of power.
Keywords: 650; Athens; institutional rigidity; institutional volatility; political and social change; regime risks; Sparta